Overexpressed GRP78 affects EMT and cell-matrix adhesion via autocrine TGF-β/Smad2/3 signaling. (July 2015) - Zhang, Lichao; Li, Zongwei; Fan, Yongsheng; Li, Hanqing; Li, Zhouyu; Li, Yaoping
Graphical abstract: Highlights: GRP78 facilitates cell-ECM adhesion by induce activation of fibronectin-integrin-β1-FAK signaling pathway. GRP78 induced cell–cell dissociation and EMT. Snail-2 plays the key role in GRP78 mediated adhesion switch and EMT. GRP78 promoted the expression and secretion of TGF-β1, and activated downstream TGF-β/Smad signaling pathway. Abstract: Glucose-regulated protein of 78 kD (GRP78) is a multifunctional protein belonging to the heat shock protein 70 family. Overexpression of GRP78 triggered by environmental and physiological stresses is positively correlated with the occurrence and progression of various tumors, but the molecular mechanisms have not been well established. The present study indicated that overexpression of GRP78 in colon cancer cells could promote cell-matrix adhesion through the upregulation of fibronectin, integrin-β1 and phosphorylated FAK. Meanwhile, it resulted in a visible epithelial–mesenchymal transition in DLD1 cells, and the Snail-2 played the key role during the process. More importantly, the data indicated that GRP78 overexpression facilitated the expression and secretion of TGF-β1, which further activated the downstream Smad2/3 signaling module to effectuate the cell-matrix adhesion and epithelial–mesenchymal transition. Taken together, this study provides a novel molecular mechanism involving in the effects of GRP78 on colon cancer metastasis.